Zinc Ions Implantation on the Surface of Commercial Papers for Antibacterial and Antifungal Applications - Khai, Dao Quang; Chi, Hoang Hieu; Duong, Nguyen Hoang; Trong, Nguyen Tam; Hanh, Mai Hong (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 4, 2023)
Recently, the demand for novel food-packaging materials with antimicrobial properties has been increasing drastically. In this report, we attempt to implant zinc ions on the surface of commercial paper sheets by using a hydrothermal method to create hydrozincite nanoflake structures. The formation of the hydrozincite nanostructure was attributed to the adsorption of zinc-ion on the calcite’s surface, a common filler used in commercial paper sheets. The zinc-modified paper sheet (PZn) demonstrated a high efficiency to inhibit C. albicans and E. coli growth. It is attributed to the release of the Zn 2+ ions into the acidic microbial medium. Along with the eco-friendliness, and biocompatible properties of the paper substrate, the PZn demonstrated a promising application in food packing.